Two new species of Platynectes Régimbart, 1879 from China with notes on other Chinese members of the genus, including a key to species (Coleoptera: Dytiscidae: Agabinae) - Jiang, Zhuo-Yin; Zhao, Shuang; Jia, Feng-Long; Šťastný, Jaroslav (Zootaxa, 2023)
Two new Platynectes species, P. maizuqii sp. nov. from Guangdong and P. pangu sp. nov. from Yunnan, are described. New records are provided for the following species: P. davidorum Hájek, Alarie, Šťastný & Vondráček, 2019 from Jiangxi, P. dissimilis (Sharp, 1873) from Guangxi, P. gemellatus Šťastný, 2003 from Hunan and Zhejiang, P. kashmiranus lemberki Šťastný, 2003 from Xizang and P. nanlingensis Šťastný, 2003 from Jiangxi. Additional records are also given for most other Chinese species. Platynectes kashmiranus kashmiranus J. Balfour-Browne, 1944 is removed from the Chinese fauna. The habitus of all and the male genitalia of most species are illustrated. An updated key to all Chinese species of Platynectes is provided.